Upaya Meningkatkan Kemampuan Membaca Al-Qur’an Melalui Metode Iqra’ pada Santriwan/Santriwati TPQ Nurussholihin Pamulang Kota Tangerang Selatan - Nur, Ita Rosita; Aryani, Rita (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
The research, entitled Efforts to improve the ability to read the Koran through the Iqra 'method of students at TPQ Nurussholihin Pamulang, South Tangerang City, for the 2021/2022 Academic Year. This study aims to determine the learning of the Iqra' method in improving the ability to read the Qur'an of students at TPQ Nurussholihin Pamulang, South Tangerang City, for the Academic Year 2021/2022. In this study, a qualitative research approach was used in order to obtain extensive and in-depth information regarding the ability to read the Qur'an through the Iqra' method at TPQ NURUSSHOLIHIN Pamulang references and triangulation of data. Based on the results of the study, it shows that the efforts made to improve the ability to read the Qur'an through the Iqra' method at TPQ Nurussholihin have the aim of making their students able to read the Qur'an through the Iqra' method and the efforts that have been made to the maximum.